Exploring primary and secondary healthcare physicians’ perceptions on pursuing population medicine as a main career: Implications for health policy and academia - Khaldoon Al-Roomi; Salman Alzayani; Amer Almarabheh; Ali M. Hamdi; Abdelhalim Deifalla (Population Medicine)
Introduction Although population medicine is a cornerstone in preventing and controlling diseases, worldwide shortages of specialists in this field continue to rise. The aim of this study is to explore physicians’ (primary and secondary healthcare) perceptions on pursuing population medicine as a main career.